RECENT INSIGHTS ON PROSPECTS OF CANCER NANOTECHNOLOGY - Sharma, Hemant K.; Kumar, Manish (Asian Journal of Pharmaceutical Research and Development, 2018)
Cancer is an extremely multifaceted illness to appreciate, since it entails manifold cellular physiological system. The mainly general cancer treatment is limited to chemotherapy, radiation and surgery. Furthermore, the untimely credit and action of cancer relics a technological block. There is an urgent require to expand novel and originaltechnology thatcould help to define tumor margins, recognize residual tumor cells and micro metastases, and decide whether a tumor has been totally removed or not. Nanotechnology has witnessed significant progress in the past few decades, and its effect is widespread nowadays in every field. Nanoparticles can be modified in numerous ways to prolong circulation, enhance drug localization, increase drug efficacy, and potentially decrease chances of multidrug resistance by the use of nanotechnology. Recently, research in the field of cancer nanotechnology has made remarkable advances. In present study review summarizes the application of various nanotechnology-based approaches towards the diagnostics and therapeutics of cancer. Key-Words:Cancer Nanotechnology, Liposomes, Targeted Delivery, Diagnosis, Nano-medicines.